2000
DOI: 10.1111/j.1469-7998.2000.tb00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the onychophoran Euperipatoides rowelli

Abstract: The reproductive biology of the ovoviviparous peripatus Euperipatoides rowelli was investigated from ®eld collections and laboratory cultures. The sexes have different demographics. The frequency distribution of individual weight is essentially L-shaped in females, but closer to normality for males: thus the sexes must exhibit different patterns of growth and/or mortality. Males are generally much smaller and rarer than females. The primary sex ratio seems to be 1:1 with equal investment in the sexes, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(86 citation statements)
references
References 25 publications
4
81
1
Order By: Relevance
“…Gleeson et al (1998) found that high levels of intraspecific COI variation also characterize Ooperipatellus insignis (11%) and Peripatoides novaezealandiae (7%). These taxa most likely represent species complexes, as has proved true for many widespread onychophoran taxa (Trewick, 1998(Trewick, , 1999(Trewick, , 2000Reid, 1996;Reid et al, 1995;Briscoe and Tait, 1995;Sunnucks and Wilson, 1999).…”
Section: Coi Sequencesmentioning
confidence: 97%
See 1 more Smart Citation
“…Gleeson et al (1998) found that high levels of intraspecific COI variation also characterize Ooperipatellus insignis (11%) and Peripatoides novaezealandiae (7%). These taxa most likely represent species complexes, as has proved true for many widespread onychophoran taxa (Trewick, 1998(Trewick, , 1999(Trewick, , 2000Reid, 1996;Reid et al, 1995;Briscoe and Tait, 1995;Sunnucks and Wilson, 1999).…”
Section: Coi Sequencesmentioning
confidence: 97%
“…Tissue was repeatedly soaked in TE9 buffer (Shiozawa et al, 1992) for several hours to leach pigments, which may act as PCR inhibitors (Sunnucks and Wilson, 1999). Tissues were then homogenized in 250 l TE9 and incubated overnight at 65°C after the addition of 30 l 20% SDS and 5 l 10 mg/ml proteinase K. Protein was precipitated with ammonium acetate, and DNA was precipitated from the supernatant with ethanol.…”
Section: Dna Extractions Primers Pcr and Sequencingmentioning
confidence: 99%
“…Dashed branches indicate putative position of key taxa missing in the analysis of Murienne et al ( 2014 ). * This mode might in fact be combined lecithotrophic/matrotrophic viviparity, which has been shown to exist in Euperipatoides rowelli (see Sunnucks et al 2000 ). " + " and " -" at each node indicate, respectively, the presence/absence of the vitelline envelope ( left ) and the chorion ( right ); question marks indicate missing data.…”
Section: Introductionmentioning
confidence: 97%
“…These embryos are often in two batches of different developmental stages: the batch closer to the ovary is at an earlier developmental stage than the batch closer to the genital opening. The reproductive biology of a closely related species is reported in Sunnucks et al (2000). The embryos were dissected out and, after removal of the egg membranes, fixed in a mixture of 1.5% paraformaldehyde and 1.5% glutaraldehyde in 0.1 M phosphate buffer, pH 7.4, for scanning electron microscopy (SEM), transmission electron microscopy (TEM), and light microscopy (LM).…”
Section: Materials and Methods Collection And Fixation Of Embryosmentioning
confidence: 99%